GW5074 Increases Microglial Phagocytic Activities: Potential Therapeutic Direction for Alzheimer’s Disease - Connor, Sarah M.; Rashid, Mamunur; Ryan, Katie J.; Patel, Kruti; Boyd, Justin D.; Smith, Jennifer; Elyaman, Wassim; Bennett, David A.; Bradshaw, Elizabeth M. (Frontiers in Cellular Neuroscience, 2022)
Microglia, the resident immune cells of the central nervous system, are responsible for maintaining homeostasis in the brain by clearing debris and are suggested to be inefficient in Alzheimer’s Disease (AD), a progressive neurodegenerative disorder for which there is no disease-modifying drug. Beside pathological approaches, unbiased evidence from genome-wide association studies (GWAS) and gene network analysis implicate genes expressed in microglia that reduce phagocytic ability as susceptibility genes for AD. Thus, a central feature toward AD therapy is to increase the microglial phagocytic activities while maintaining synaptic integrity. Here, we developed a robust unbiased high content screening assay to identify potential therapeutics which can reduce the amyloid-beta (Aβ1-42) load by increasing microglial uptake ability. Our screen identified the small-molecule GW5074, an inhibitor of c-RAF, a serine/threonine kinase, which significantly increased the Aβ1-42 clearance activities in human monocyte-derived microglia-like (MDMi) cells, a microglia culture model that recapitulates many genetic and phenotypic aspects of human microglia. Notably, GW5074 was previously reported to be neuroprotective for cerebellar granule cells and cortical neurons. We found that GW5074 significantly increased the expression of key AD-associated microglial molecules known to modulate phagocytosis: TYROBP, SIRPβ1 and TREM2. Our results demonstrated that GW5074 is a potential therapeutic for AD, by targeting microglia.